Dominance via Diplomacy: Analysing India’s Assertive Regional Strategy in South Asia - Ghalib, Jehanzaib; Khan, Ahmad (Journal of security and strategic analysis, 2025)
Throughout its historical evolution, India has positioned itself as a dominant South Asian state. Under the guise of nationalism and to promulgate its influence, India has intervened in the internal affairs of other regional states. Cloaked in strategic objectives, economic diplomacy, and political cooperation, India aims to expand its influence in neighbouring states. Through the central tenets of John J. Mearsheimer’s ‘offensive realism,’ this paper analyses how India has been assertive towards other South Asian countries, utilising diplomacy to achieve its dominance. Contrary to this dominance-driven approach, recent political developments in Bangladesh, Nepal, Sri Lanka, and the Maldives reflect India’s efforts to project itself as ‘big brother’ and vishvamitra (friend of all) in South Asia and beyond. The paper is developed on qualitative methodology to analyse the possible objectives behind India’s assertive foreign policy in South Asia. While India projects itself as a well-wisher of the South Asian countries, the objectivity reveals that India’s goodwill towards the respective states primarily serves to maximise its political, strategic, and economic leverage over those states. This paper analyses the growing contradiction between India’s projected image of diplomacy as a cooperative regional leader and its increasingly assertive and interventionist foreign policy to achieve dominance in South Asia.